KAJIAN ATAS DRAF STANDAR PENDIDIKAN AKUNTANSI (SPAI) 2008: INDIKASI SEMAKIN BERATNYA AKREDITASI PRODI AKUNTANSI DI MASA YANG AKAN DATANG - Elizabeth Tiur Manurung (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Globalization now have impact on the competition between Indonesian and Foreign Accountants. More foreign accountants now have their jobs in Indonesia which makes the competition even fiercer. With the situation at hand, the Indonesian accountants must up-grade their competencies to the same quality or level with those of foreigners, in order that they be able to win the competition. Certainly, this duty- to standardize the qualification of graduate-is assumed by the Accountant Bodies / Institution, and the university role here is to meet the minimum qualification of graduates. For that reason, the draft of Accounting Education Standard (2008), has been established by The Indonesian Accountant Institution (lAl), Accounting Lecturer Compartment. This draft is also the answer for the globalization competition. The further explanation will contain the elaboration of several key points of the draft, and analysis of the impact on education institution, especially on the quality assessment in the future.